Habituation of the Interlimb Reflex (ILR) Over the Biceps Brachii Muscle After Electrical Stimuli Over the Sural Nerve - Alaid, Ssuhir; Emmer, Alexander; Kornhuber, Malte Erich (Frontiers in Neuroscience, 2019)
Up to now relatively little is known about interlimb reflexes (ILR). Especially it is not well known whether ILR may habituate or not to subsequent stimuli. The main aim of the present investigation was to explore the short term habituation behaviour of ILR. The electromyogram was recorded over the tonically active biceps brachii muscle in 11 healthy subjects contralateral and ipsilateral to supramaximum electrical stimuli (9-12 mA) that were delivered at 1.0 and 0.4 Hz over the left sural nerve. In addition, a selective averaging method was used to investigate the influence of preceding stimuli on the ILR. Thus, 30 blocks of 3 subsequent stimuli were used. All 1st ILR of each block were averaged together. Averages were also obtained for 2nd and 3rd ILR. While ILR amplitudes gained significantly both ipsilateral and contralateral to the stimulus (p < 0.05) after train stimuli as compared with single stimuli, ILR amplitudes showed a significant decrease at 1.0 Hz versus 0.4 Hz stimuli. ILR amplitudes decreased significantly after the 2nd and 3rd stimulus relative to the 1st (p < 0.05). ILR can be recorded bilaterally remote from the stimulus site. Furthermore, ILR show clear short term habituation behaviour. Thus, ILR show features reminiscent of a startle response.